2013
DOI: 10.1002/ange.201305254
|View full text |Cite
|
Sign up to set email alerts
|

Barium Dibenzopentalenide as a Main‐Group Metal η8 Complex: Facile Synthesis from 1,4‐Dilithio‐1,3‐butadienes and Ba[N(SiMe3)2]2, Structural Characterization, and Reaction Chemistry

Abstract: Transmetallierung von 1,4‐Dilithio‐1,3‐butadienen mit Ba[N(SiMe3)2]2 führte zu Bariumdibenzopentaleniden, deren Struktur röntgenkristallographisch untersucht wurde. Erste Reaktivitätsstudien der so erhaltenen Bariumdibenzopentalenide zeigen präparativ nützliche Anwendungen auf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
(12 reference statements)
0
11
0
7
Order By: Relevance
“…[12] Dilithio reagent 1a (R = Me) was then used as the example to test our proposal. [12] Dilithio reagent 1a (R = Me) was then used as the example to test our proposal.…”
Section: Methodsmentioning
confidence: 99%
“…[12] Dilithio reagent 1a (R = Me) was then used as the example to test our proposal. [12] Dilithio reagent 1a (R = Me) was then used as the example to test our proposal.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Ein Beispiel ist das ortho-Bromphenylacetylen 14, das unter den in Schema 4 gezeigten Bedingungen in 46 % Ausbeute das 5,10-disilylierte Dibenzopentalen 15 liefert. Dibenzopentalendihalogenide (11) aus Ethinylbenzolen (8) nach Saito et al [5] Schema 2. [8] Die gegenwärtig vielfältigste und in hçchster Ausbeute verlaufende Dimerisierung dieses Typs ist von Tilley und Levi vorgestellt worden.…”
Section: Angewandte Highlightsunclassified
“…[1] Als antiaromatische 4n-Kohlenwasserstoffe -formal handelt es sich bei ihnen um "kurzgeschlossene" und daher planare Cyclooctatetraenesind viele dieser Substanzen äußerst kurzlebig und gehen beispielsweise leicht Dimerisierungen ein. [5] In einer anderen, katalytischen CH-Aktivierungsroute haben Maekawa et al diverse Arylacetylene in die entsprechenden substituierten Dibenzopentalene umgewandelt. 59 8C), den ersten isolierbaren Vertreter dieser Substanzklasse herzustellen.…”
unclassified
See 1 more Smart Citation
“…

Organolithium compounds can behave as reductants but never as oxidants in redox reactions.Reported herein is that 1,4-dilithio-1,3-butadienes reacted with [Ni(cod) 2 ]( cod = 1,5cyclooctadiene) to deliver dilithionickeloles.S ingle-crystal Xray structural analysis revealed ac oplanar structure of dilithionickeloles with an averaging of bond lengths.X PS data confirmed the oxidation state of Ni in dilithionickeloles was Ni 2+ . [2] It was reported that nickel(0) complexes could react with stoichiometric amounts of alkyllithium reagents to afford Ni 0 ate complexes. [1] We have been working on the reaction chemistry and synthetic applications of dianions with p-conjugation, especially 1,4-dilithio-1,3-butadienes (dilithio reagents for short).

…”
mentioning
confidence: 99%